STIKLELE ALTERNATIF DIVERSIFIKASI OLAHAN LELE (Clarias SP) TANPA LIMBAH BERKALSIUM TINGGI - Dyah Ilminingtyas Wahyu Handayani; Diah Kartikawati (Serat Acitya, 2015)
Catfish was favored by many people, but so far their utilization has beenlimited to edible meat whereas the meat section of the catfish was less than 40%.  Bones and head catfish is a mineral-rich waste, especially calcium. The diversification attempt of proccessed catfish by using all parts of catfish was an effort to optimize the utilization of catfish, increasing the economic value and improve the nutritional value, mainly calcium. The purpose of this study was to optimized the utilization of catfish as foodstuffs by way of diversification of processed catfishto makesticks without leaving waste . The experimental design used was a complete randomized design (CRD) of one factors, namely the use of three types of raw material catfish include: meat catfish , catfish intact and waste bones and head catfish.The parameters investigated were the levels of calcium, protein, fat, water, ash, carbohydrate and hedonic test. Data were analyzed using analysis of variance (ANOVA) followed by Duncan test . The treatment of different catfish raw material usage were catfish meat, whole catfish and waste of bones and head on making sticks successively lowered the levels of the protein but on the other hand can increased the levels of calcium . This treatment affected the levels of protein, fat, water, ash, carbohydrates and calcium. Stick protein content between 9.3 - 13.63%, sticks calcium levels ranged between 0,08 - 2.74. The results of organoleptic test on sticks hedonic scale showed the sticks product which made ​​from whole fish and fish waste meat bones and head were the most preferred.